KAJIAN TOKOH ISLAM KLASIK PERTENGAHAN: PEMIKIRAN AL-GHAZALI TENTANG PENDIDIKAN ANAK - Lilif Mualifatul Khorida Filasofa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
Education as a form of knowledge transformation especially the problem of religious education Al-Ghazali is one of the classical Muslim figures who are experts in education. The method used in this research is literature study with data sourced from scientific articles, books, and other literature sources. The data analysis technique is done by data reduction, this is done in order to filter existing data to prevent data accumulation. From the research it can be obtained in the form, education must start early, even when a child is still in the womb, educators must love their students and in the book ihya 'umuluddin there are nine important points in children's education.